Relationship between biomarkers and findings on low-dose computed tomography in hospitalised patients with acute exacerbation of COPD. Issue 2 (20th June 2022) - Prins, Hendrik J.; Duijkers, Ruud; Kramer, Gerdien; Boerhout, Els; Rietema, Floris J.; de Jong, Pim A.; Schoorl, Marianne I.; van der Werf, Tjip S.; Boersma, Wim G.
Background: Acute exacerbations of COPD (AECOPD) and community acquired pneumonia (CAP) often coexist. Although chest radiographs may differentiate between these diagnoses, chest radiography is known to underestimate the incidence of CAP in AECOPD. In this exploratory study, we prospectively investigated the incidence of infiltrative changes using low-dose computed tomography (LDCT). Additionally, we investigated whether clinical biomarkers of CAP differed between patients with and without infiltrative changes. Methods: Patients with AECOPD in which pneumonia was excluded using chest radiography underwent additional LDCT-thorax. The images were read independently by two radiologists; a third radiologist was consulted as adjudicator. C-reactive protein (CRP), procalcitonin (PCT), and serum amyloid A (SAA) at admission were assessed. Results: Out of the 100 patients included, 24 had one or more radiographic abnormalities suggestive of pneumonia. The interobserver agreement between two readers (Cohen's κ) was 0.562 (95% CI 0.371–0.752; p<0.001). Biomarkers were elevated in the group with radiological abnormalities compared to the group without abnormalities. Median (interquartile range (IQR)) CRP was 76 (21.5–148.0) mg·L −1 compared to 20.5 (8.8–81.5) mg·L −1 (p=0.018); median (IQR) PCT was 0.09 (0.06–0.15) µg·L −1 compared to 0.06 (0.04–0.08) μg·L −1 (p=0.007); median (IQR) SAA was 95 (7–160) µg·mL −1 compared to 16 (3–89) µg·mL −1 (p=0.019). Sensitivity and specificity for all three biomarkers were moderate for detecting radiographic abnormalities by LDCT in this population. The area under the receiver operating characteristic curve was 0.66 (95% CI 0.52–0.80) for CRP, 0.66 (95% CI 0.53–0.80) for PCT and 0.69 (95% CI 0.57–0.81) for SAA. Conclusion: LDCT can detect additional radiological abnormalities that may indicate acute-phase lung involvement in patients with AECOPD without infiltrate(s) on the chest radiograph. Despite CRP, PCT and SAA being significantly higher in the group with radiological abnormalities on LDCT, they proved unable to reliably detect or exclude CAP. Further research is warranted. LDCT-thorax can detect additional radiological abnormalities in patients with AECOPD after excluding CAP using chest radiography. Biomarkers are significantly elevated in patients with abnormalities, but are not able to reliably exclude these changes. https://bit.ly/3KAsBap